Konsep Aliran Filsafat Pendidikan (Esensialisme) - Ilmiah, Nur; Apriliani, Gita; R, Raudah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
the concept of the educational philosophy of Essentialism, which emphasizes essential and fundamental knowledge for individual development. With a historical background that can be traced back to the thoughts of Plato and Aristotle, Essentialism highlights the importance of eternal and universal knowledge such as mathematics, natural sciences, and ethics in shaping character and deep understanding. Through a systematic approach and focus on the essence of human beings, Essentialism offers a different perspective in the world of education.